Deconstructing The Pedagogical Praxis of Christian Educators: A Hermeneutical Analysis of Matthew's Gospel - Franspebri .P, Yoel; Yulia , Tantri (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
Contemporary Christian religious education necessitates a theoretically robust understanding of pedagogical roles grounded in theological frameworks. While previous research has explored teachers' responsibilities from educational perspectives, systematic analyses of biblical texts as foundational pedagogical sources remain underdeveloped. This study examines the multidimensional roles of Christian religious educators through a hermeneutical analysis of Matthew's Gospel, identifying pedagogical paradigms that can inform contemporary educational praxis. Employing a qualitative hermeneutical approach, this research systematically analyzed the Gospel of Matthew using critical exegetical methods and thematic content analysis. The investigation incorporated intertextual analysis, historical-critical interpretation, and phenomenological reduction to identify pedagogical frameworks embedded within the Matthean narrative. The analysis revealed four distinct yet interconnected pedagogical dimensions within Matthew's Gospel: (1) Teachers as transformative agents implementing instructional, kerygmatic, and restorative functions within communal contexts; (2) Teachers as dialogical facilitators demonstrating attentive listening, critical engagement, patience, and impartiality; (3) Teachers as ethical mentors providing counsel, cultivating responsibility, and modeling virtuous conduct; and (4) Teachers as spiritual catalysts inspiring vocational consciousness and sustaining theological resilience. These findings suggest that effective Christian religious education requires an integrated pedagogical approach that transcends mere knowledge transmission to encompass transformative, facilitative, mentoring, and catalytic functions. This research contributes to educational theology by providing a biblically-grounded theoretical framework for contemporary Christian pedagogical practice.